A Systematic Literature Review of Science and Physics Education Teaching Regarding Oscillations - Yudi Kurniawan; Andi Suhandi; Achmad Samsudin; Nguyen Thi Thanh Xuan (Universitas Pendidikan Indonesia, 2024)
This article provides a detailed analysis of the various methods used in physics classrooms to teach oscillation and its related concepts. We thoroughly searched reputable databases, including Scopus and Web of Science. We analyzed 50 articles published between 2018 and 2023 using content analysis techniques such as elimination, classification, and grouping into themes. Our unit of analysis was the articles' methods, results, and conclusions. The results of this study are: (1) The trends in the development of research on the topic of oscillation and its derivatives from 2018 to 2023 indicate a declining interest. (2) During the period from 2018 to 2023, Indonesia emerged as the primary contributor to research on the topic of oscillation; (3) From 2018 to 2023, researchers predominantly focused on the topic of pendulum in the field of oscillation research (4) The most prevalent method for imparting oscillation content and its derivatives employed by researchers between 2018 and 2023 was experimentation, and (5) The most prevalent type of empirical research conducted on the topic of oscillation between 2018 and 2023 was pure research involving laboratory experiments. This systematic literature review is a foundation for developing various learning tools such as teaching materials, technology-based instructional media development, and primarily instruments related to oscillation and its derivatives. Overall, this systematic review highlights the need for more research on effective teaching methods for oscillation and provides practical insights for educators and researchers alike.